Interplay between Conformation and Crystal Packing in Aryl Propargyl Ethers: Structural and Spectroscopic Properties of 2‐(prop‐2‐yn‐1‐yloxy)acene Derivatives. Issue 34 (9th September 2019) - Saeed, Aamer; Shehzadi, Syeda Aaliya; Bolte, Michael; Franca, Carlos A.; Erben, Mauricio F.
Abstract: The 2‐(prop‐2‐yn‐1‐yloxy)naphthalene (compoundI ) and 1‐nitro‐2‐(prop‐2‐yn‐1‐yloxy)benzene (compoundII ) were prepared in excellent yields by the reaction of propargyl bromide with 2‐naphthol and 2‐nitrophenol, respectively. Structural and conformational properties of both compounds have been analyzed using a combined approach including single‐crystal X‐ray diffraction and quantum chemical calculations. Two forms are found to be stable and nearly isoenergetic conformers, depending on the mutual orientation of the C≡C triple bond and the O–C single bond of the prop‐2‐yn‐1‐yloxy group. The gauche conformation is the most stable form for the vacuum isolated species, with the anti conformation higher in energy by 1.00 and 1.89 kcal/mol computed at the M06‐2X/6‐311++G(d, p) level of approximation, forI andII, respectively. The gauche form is observed in the crystal ofI but the nearly planar anti conformation is adopted in the crystalline phase of compoundII . The occurrence of C–H⋅⋅⋅π and C–H⋅⋅⋅O intermolecular interactions involving the acidic ‐C≡C–H hydrogen donor and ‐C≡C‐ and ‐OCH2 – acceptors is discussed. Furthermore, vibrational features of the prop‐2‐yn‐1‐yloxy moiety are analyzed by infrared and Raman spectroscopy. The UV‐Vis spectrum shows the presence of well‐defined absorption at ca. 280 and 320 nm assigned to the π→π* transitions in the naphtyl/benzyl and prop‐2‐yn‐1‐yloxy groups, respectively. Abstract : Two closely related molecules containing the prop‐2‐yn‐1‐yloxy group are studied. Two nearly isoenergetic conformations are computed, depending on the mutual orientation of the C≡C triple bond and the O–C single bond. For both compounds, the gauche conformation is the most stable form for the vacuum isolated species, with the anti conformation higher in energy. Surprisingly, the gauche form is observed in the crystal of I, while the anti conformation is adopted for compoundII .